PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 30 TELUK LANCAR KECAMATAN BANTAN - Zulkifli, Zulkifli; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of social subject. It show from 20 student’s, 12 students ( 60 % ) have lower score, and it is only 8 student’s ( 40 % ) have average score 68,3. The KKM of this school is 65. According to that problem, the research by implementing cooperative learning model Take And Give. In cycle I, the persentage of teachers activity in first meeting is adquate 75,00%. In second meeting, teachers activity significantly increased to 79,16% with good category. In cycle 2, first meeting was in good category 83,33% and second meeting indicated a very good category 91,66%. Meanwhile, the activity of student’s also improved. In cycle I indicated 58,33% in adequate category and in cycle 2 has increased up to 75,00% with good category. In cycle 2, first meeting, the activity of student’s has been increasing to 87,5% with good category and second meeting indicated very good category 95,83%. An average score score of student’s learning result before implementation is 68,3. It increased to 74,25 in cycle I, and 82,4 in cycle 2. In clasical completennes, cycle I and cycle 2 were achieved. In conclussion, implementation cooperative learning model Take And Give can improve student’slearning result of five grade students of SD Negeri 30 Teluk Lancar Kecamatan Bantan in social subject.Key words: Cooperative model guided teaching, learning result of social subject